Association between Malnutrition and Depression in Elderly People in Razavi Khorasan: A Population Based-Study in Iran - N Mokhber; MR Majdi; M Ali-Abadi; MT Shakeri; M Kimiagar; R Salek; P Ahmadi Moghaddam; A Sakhdari; M Azimi-Nezhad; M Ghayour-Mobarhan; SS Soluti (Tehran University of Medical Sciences, 2011)
Background: To determine the prevalence of malnutrition and depression in free-living elderly people and their relationships (If any) in Razavi Khorasan, Iran 2007. Methods: To evaluate nutritional status, we used Mini Nutritional Assessment (MNA) method in free-living elderly people (n=1565 using cluster sampling, 720 males and 845 females, aged≥ 60 yr) and their relationship to Socio Economic Conditions (SECs).  Based on the final scores, our patients were classified into three groups: score 17-23.5 (at risk for malnutrition), score less than 17 (with malnutrition), and score 24-30 (well nourished). To determine the mood status (here depression), we used Geriatric Depression Score (GDS). According to this score our participants turned out to be in two distinct groups: depressed (score ≥8) and non-depressed (score< 8). Results: From the total subjects entered the study (1495), 22.07% were depressed and 11.5% and 44% were malnourished or at risk of malnutrition respectively. In depressed group, the prevalence of malnutrition was 14.5% (48 out of 330) and the prevalence of "at risk of malnutrition" was 45.8%, whereas the prevalence of malnutrition and at risk of malnutrition in non-depressed population were 10.6% and 43.3% respectively. From the aforemen-tioned information we have concluded that there is a significant statistical difference between the prevalence of malnutrition in depressed and non-depressed individuals (P= 0.047). Conclusions: With respect to the high rate of vegetative symptoms in elderly depressed individuals, malnutrition would have a higher prevalence in the depressed people.